East Asia in World Trade: The Decoupling Fallacy, Crisis, and Policy Challenges - Prema-chandra Athukorala; Archanun Kohpaiboon (FIW - Research Centre International Economics, 2010)
This paper examines the export experience of China and other East Asian economies in the aftermaths of the global financial crisis against the backdrop of pre-crisis trade patterns. The analysis is motivated by the decoupling' thesis, which was a popular theme in the Asian policy circles in the lead-up to the onset of the recent financial crisis, and aims to probe three key issues: Was the East Asian trade integration story that underpinned the decoupling thesis simply a statistical artifact or the massive export contraction caused by an overreaction of traders to the global economic crisis and/or by the drying up of trade credit, which overpowered the cushion provided by intra-regional trade? What are the new policy challenges faced by the East Asian economies? Is there room for an integrated policy response that marks a clear departure from the pre-crisis policy stance favoring export-oriented growth? The findings caution against a possible policy backlash against openness to foreign trade arising from the new-found enthusiasm for rebalancing growth, and make a strong case for a long-term commitment to non-discriminatory multilateral and unilateral trade liberalization.
Keywords: F15; F23; O53; 330; global financial crisis; global production sharing; production networks; China